2003
DOI: 10.1002/bjs.4179
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe acute pancreatitis

Abstract: Recent evidence has helped to clarify the roles of computed tomography, endoscopic retrograde cholangiopancreatography, prophylactic antibiotics, enteral feeding and fine-needle aspiration for bacteriology in the management of acute pancreatitis. Despite a relative shortage of prospective randomized trials there has been a significant change in the surgical management of acute pancreatitis over the past 20 years. This change has been away from early aggressive surgical intervention towards more conservative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
2
6

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 133 publications
0
81
2
6
Order By: Relevance
“…Guidelines (2, 4, 6, 7) and review articles (9)(10)(11)(12) have generally suggested that surgery be performed promptly or have left unsaid the exact timing of surgery. However, one recent guideline specified that surgical debridement be performed for patients with infected necrosis who are "septic" (3).…”
Section: Level Of Evidence: IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines (2, 4, 6, 7) and review articles (9)(10)(11)(12) have generally suggested that surgery be performed promptly or have left unsaid the exact timing of surgery. However, one recent guideline specified that surgical debridement be performed for patients with infected necrosis who are "septic" (3).…”
Section: Level Of Evidence: IIImentioning
confidence: 99%
“…These and subsequent guidelines (2-7) have undergone periodic review (6,(8)(9)(10)(11)(12)(13) in accordance with advances that have been made in the diagnosis and treatment of acute pancreatitis. Guidelines for clinical practice are intended to apply to all health-care providers who take care of patients with acute pancreatitis and are intended to be flexible, and to suggest preferable (but not the only) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with mild to moderate pancreatitis, gastrointestinal rest with adequate fluid resuscitation is usually sufficient initial management. The oral route for feeding should be re-established as soon as the nausea subsides, and provided that the pain does not reappear upon feeding (1,2,6,52,53,73,74,75).…”
Section: Pain Controlmentioning
confidence: 99%
“…Recent studies of the physiology of the gastrointestinal tract have demonstrated benefits of enteral feeding especially related to its trophic effects on the intestinal tract (53,74,76,77).…”
Section: Pain Controlmentioning
confidence: 99%
See 1 more Smart Citation